Bioactive Decellularized Extracellular Matrix Derived from 3D Stem Cell Spheroids under Macromolecular Crowding Serves as a Scaffold for Tissue Engineering. Issue 11 (22nd April 2021) - Chiang, Cheng‐En; Fang, Yi‐Qiao; Ho, Chao‐Ting; Assunção, Marisa; Lin, Sheng‐Ju; Wang, Yu‐Chieh; Blocki, Anna; Huang, Chieh‐Cheng
Abstract: Scaffolds for tissue engineering aim to mimic the native extracellular matrix (ECM) that provides physical support and biochemical signals to modulate multiple cell behaviors. However, the majority of currently used biomaterials are oversimplified and therefore fail to provide a niche required for the stimulation of tissue regeneration. In the present study, 3D decellularized ECM (dECM) scaffolds derived from mesenchymal stem cell (MSC) spheroids and with intricate matrix composition are developed. Specifically, application of macromolecular crowding (MMC) to MSC spheroid cultures facilitate ECM assembly in a 3D configuration, resulting in the accumulation of ECM and associated bioactive components. Decellularized 3D dECM constructs produced under MMC are able to adequately preserve the microarchitecture of structural ECM components and are characterized by higher retention of growth factors. This results in a stronger proangiogenic bioactivity as compared to constructs produced under uncrowded conditions. These dECM scaffolds can be homogenously populated by endothelial cells, which direct the macroassembly of the structures into larger cell‐carrying constructs. Application of empty scaffolds enhances intrinsic revascularization in vivo, indicating that the 3D dECM scaffolds represent optimal proangiogenic bioactive blocks for the construction of larger engineered tissue constructs. Abstract : Applying of macromolecular crowding (MMC) to 3D spheroid cultures of mesenchymal stem cell (MSC) achieves the accumulation of extracellular matrix (ECM) and associated bioactive components. After decellularization, the resulting 3D decellularized ECM constructs have a well‐preserved microarchitecture of the structural ECM components and can be repopulated by cells for directing their macroassembly into larger cell‐carrying tissue engineering constructs.